Colitis Tuberculosis - Budi Tan Oto; Ahmad Fauzi; Ari Fahrial Syam; Marcellus Simadibrata; Murdani Abdullah; Dadang Makmun; Chudahman Manan; Abdul Aziz Rani; Daldiyono Daldiyono (The Indonesian Society for Digestive Endoscopy, 2010)
Tuberculosis (TB) is a significant public health problem worldwide. Indonesia is a country with the third highest prevalence of TB in the world after China and India. TB infection can attack all organs of the human body. TB in digestive system is one of the extrapulmonary TB manifestations and comprises of 3- 16% of all extrapulmonary TB cases. This type of TB may affect digestive system, peritoneum, mesentery lymphatic glands, liver, and spleen. Digestive system is affected in 66-75% of patients with abdominal TB. The ileocaecal region is most commonly affected. The manifestation of abdominal TB is not specific. Precise diagnostic approach and supporting results are needed to determine final diagnosis. However, there is no single examination adequate enough to diagnose abdominal TB. If the diagnosis can be established early, this disease could then be managed with conventional anti-TB drugs. Treatment for both 6-9 months period and 18-24 months period has been proven effective in management of extrapulmonary TB. In countries with high abdominal TB prevalence, initiation of anti-TB therapy is allowed if there are the clinical features present. Diagnosis can be determined when the patient has therapeutic response against the the anti-TB treatment. Keywords: tuberculosis, colitis, extrapulmonary, antituberculosis drugs